A mechanism to enhance bicycle conspicuity and visibility and increase detection distances: New insights into bicycle safety. (July 2021) - Abdur, Rahman; Aya, Kojima; Teppei, Kato; Hisashi, Kubota
Abstract: Poor sensory conspicuity and poor visibility of bicycles are key factors that correlate strongly with bicycle-vehicle accidents. Although researchers have explored how to improve detection distances, i.e., the distances from which bicycles can be recognized by other road users, there is a dearth of research on ways to signal bicyclists' presence on the road. This study investigates how to enhance, at minimum cost, the level of visibility and sensory conspicuity of bicycles; it also considers ways to signal their presence to other road users, without necessitating any active behavior by bicyclists themselves. In the first study, the level of visibility of 6 rear-end components of bicycles was analyzed according to Adrian's model; the sensory conspicuity of these same components was analyzed via respondent perceptions in conditions of sunlight, twilight with no car headlights, twilight with car headlights, and night with car headlights. The level of visibility and sensory conspicuity of the 6 rear-end components were compared with considering angular size of the components under 4 lighting conditions. The level of visibility of the rear fender was good under sunlight and night-time conditions; in other conditions, the level of visibility was directly affected by painting the fender a silver color with reflectivity and also by the fender's angular size. However, the rear tire, among the 6 components tested, had a higher visible area when used with a short fender; it also produced rotational effects during riding conditions with no extra effort by the cyclists. In the second study, adhesive tape with specific patterns and 6 different color combinations were applied to the rear tire of a bicycle under the same lighting conditions, with the aim of creating a strong signal of the bicycle's presence for other road users. Among the 6 combinations, white stripes overlaid on the color red provide an optimal combination in terms of detection distance. The mean detection distance of white stripes on red in sunlight was 138.67 m, 94.67 m in twilight without car headlights, 94 m in twilight with car headlights, and 53.67 m at night with car headlights. In addition, this combination strongly signals the presence of the bicycle to other road users with no extra effort by the cyclists, thereby reducing the likelihood of drivers looking but failing to see bicycles. In sum, the study recommends that bicyclists install white stripes overlaid on red, in order to increase visibility and conspicuity and signal the presence of their bicycles, thereby reducing the likelihood of cyclist-vehicle collisions. Highlights: Assess the visibility and conspicuity of rear-end components of bicycle Color modify of tire of bicycle to evaluate the enhancement of detection distance White stripes overlaid on red (WRED) color combination increase the visibility and conspicuity and signal of presence of bicycle